Nursing diagnosis handbook : an evidence-based guide to planning care - Ackley, Betty J.; Ladwig, Gail B. (Mosby Elsevier, 2014)
With the NANDA-I approved nursing diagnoses, this title shows you how to build customized care plans using a three-step process: assess, diagnose, and plan care. It includes suggested nursing diagnoses for over 1,300 client symptoms, medical and psychiatric diagnoses, diagnostic procedures, surgical interventions, and clinical states